The Attitudes and Values Behind the Mobility Habits of the Helsinki Capital Region Inhabitants - Alho, Anni (fi=Turun yliopisto|en=University of Turku|, 2017)
Climate change mitigation puts pressure on societies to change their mobility habits. People are at the centre of this change and, therefore, it is crucial to understand the determinants behind people’s mobility habits. The objective of this master’s thesis research is to find out what kinds of values and attitudes guide the daily mobility habits of the Helsinki capital region inhabitants. The research was conducted as an assignment for MaaS Global and the aim is to provide information that can support development of the Mobility as a Service (MaaS) concept, which is seen as a one of the ways of making the transport sector more sustainable. The data were collected with a survey posted to the social media channels of the Helsinki, Vantaa and Espoo municipalities and to an informal Facebook page for Vantaa inhabitants. The data were analysed mainly with statistical methods. The answers were grouped into seven mobility segments that were formed based on the primary and secondary modes of transport used by the survey respondents. The mobility segments are (1) active users of public transport, (2) primary car users / secondary public transport users, (3) primary public transport users / secondary car users, (4) sporty car users, (5) sporty public transport users, (6) committed car users, and (7) pedestrians and cyclists. The mobility segments form the basis for the analysis. The results show that most people have positive attitudes towards walking and cycling. As modes of transport, cycling and walking are also seen as beneficial forms of exercise. However, positive attitudes towards walking and cycling are not necessarily reflected in actual mobility habits because some other values, such as comfort, are higher on a person’s value hierarchy and, therefore, guide them to choose other modes of transport, such as a private car or public transport. In addition to comfort, the reasons for using a private car are usually practical, whereas status and image related reasons do not have much influence on private car usage. Among active public transport users, pedestrians and cyclists, and sporty public transport users, there are people who have negative attitudes towards private car usage – they also see that a private car is not suitable for their image. Most people have neither status nor safety related obstacles for using public transport. The group of committed car users is rather small and most people combine different modes of transport. The opportunity to combine different modes of transport is seen as a way to achieve freedom of mobility.